2010
DOI: 10.1128/mcb.00240-10
|View full text |Cite
|
Sign up to set email alerts
|

TIN2-Tethered TPP1 Recruits Human Telomerase to Telomeres In Vivo

Abstract: Recruitment to telomeres is a pivotal step in the function and regulation of human telomerase; however, the molecular basis for recruitment is not known. Here, we have directly investigated the process of telomerase recruitment via fluorescence in situ hybridization (FISH) and chromatin immunoprecipitation (ChIP). We find that depletion of two components of the shelterin complex that is found at telomeres-TPP1 and the protein that tethers TPP1 to the complex, TIN2-results in a loss of telomerase recruitment. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
232
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(243 citation statements)
references
References 57 publications
9
232
1
1
Order By: Relevance
“…At the telomere, Tpp1 and Tin2 are important for telomerase recruitment or its retention, as depletion of either of these factors reduces (but does not abolish) telomerase association with telomeres (Abreu et al 2010). Depletion and rescue studies further identified the aminoterminal OB-fold of Tpp1 as important for telomerase recruitment (Abreu et al 2010), a domain that was found to also interact with telomerase in extracts (Xin et al 2007).…”
Section: Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the telomere, Tpp1 and Tin2 are important for telomerase recruitment or its retention, as depletion of either of these factors reduces (but does not abolish) telomerase association with telomeres (Abreu et al 2010). Depletion and rescue studies further identified the aminoterminal OB-fold of Tpp1 as important for telomerase recruitment (Abreu et al 2010), a domain that was found to also interact with telomerase in extracts (Xin et al 2007).…”
Section: Mammalsmentioning
confidence: 99%
“…Depletion and rescue studies further identified the aminoterminal OB-fold of Tpp1 as important for telomerase recruitment (Abreu et al 2010), a domain that was found to also interact with telomerase in extracts (Xin et al 2007). Whether telomerase recruitment is regulated in mammals by Atm or Atr, as in fission and budding yeast, is unknown, nor is it clear if in addition to Tpp1 other factors contribute to recruitment.…”
Section: Mammalsmentioning
confidence: 99%
“…For DNA extraction, the QIAquick PCR Purification kit (Qiagen) was used. Telomeric and Alu-repeat DNA were detected successively 37 . Telomeric DNA was detected using a probe 4 that was generated as follows: a template mixture of 1-5 kb long telomeric DNA fragments was synthesized by ligating double-stranded telomeric DNA oligonucleotides ((TTAGGG) 5 , (CCCTAA) 5 ) that were amplified by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the TPP1-POT1 complex can recruit and stimulate telomerase activity through direct interaction between TPP1 and telomerase. This interaction depends on the OB fold of TPP1 (15)(16)(17)(18)20). Recent studies have identified the residues that are required for the interface of TPP1-telomerase interaction (20)(21)(22).…”
Section: Phosphorylation Of Tpp1 S111 Is Implicated In Telomere Lengthmentioning
confidence: 99%
“…Of the six proteins, TPP1 contains an N-terminal oligonucleotide-and oligosaccharide-binding (OB) fold and is tethered to telomeres through interactions with telomere DNA binding proteins TRF1, TRF2, and POT1 (13,14). Work from us and others has shown that the TPP1 OB fold interacts with the telomerase and is required for telomere recruitment of telomerase and high telomerase processivity (15)(16)(17)(18)(19). Recently, key residues that define the interface for human TPP1 OB foldtelomerase interaction have been identified (20)(21)(22).…”
mentioning
confidence: 99%